The Influence of Competence, Professionalism and Integrity on Audit Quality with Auditor Ethics as a Moderating Variable - Setyadi, Setyadi; Heniwati, Elok; Hamzani, Umiaty; Desyana, Gita; Indah, Djunita Permata (STMIK Widya Cipta Dharma, 2024)
This study aims to evaluate the influence of professionalism and integrity on audit quality and analyze the role of auditor ethics as a moderating variable. The research was conducted at the Inspectorates of Mempawah Regency and Bengkayang Regency, involving 30 auditors as the sample. Data were collected through questionnaires and analyzed using the path analysis method with WarpPLS 7.0 software. The results indicate that professionalism and integrity significantly influence audit quality, while competence does not have a significant effect. Furthermore, auditor ethics moderates the relationship between integrity and professionalism on audit quality but does not moderate the relationship between competence and audit quality. The findings highlight the critical role of professionalism, integrity, and auditor ethics in enhancing audit quality. This study provides both practical and theoretical contributions to fostering more transparent and accountable regional financial governance.